Student’s willingness to pay at eateries around UiTM Dungun - Nordin, Siti Nur Hanani; Mohd Yusoff, Nur Ainina; Mohd Aris, Muhammad Muzhaffar (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Given that students are lacking a source of income and only a few receive financial assistance from particular organizations, they must cultivate prudent spending habits in their daily lives, which can influence their food shopping decisions. Consequently, various characteristics may influence students’ propensity to pay for meals at dining establishments and are regarded as the primary element in numerous researches connected to willingness to pay. The main objective of this study is to ascertain the correlation between food quality, price and value, and the Dineserv components with students' willingness to spend at dining establishments in or near UiTM Dungun. This study was quantitatively conducted at UiTM Dungun, Terengganu. The findings indicate that only one aspect, specifically food quality, significantly correlates with students' willingness to spend, as the majority of students identified this component as influential in their purchasing decisions. This study's implications can improve the restaurant's comprehension of students' willingness to pay for meal quality, pricing, value, and Dineserv service quality, aiding in the assessment prior to establishing accurate menu pricing.